Интерполяция функции расчета площади правильных многоугольников - Волкова, М. А. (ХНУРЭ, 2012)
In the paper the theoretical and experimental study of a new approach to calculating the area of regular polygons by the radius of the circumscribed circle.
Keywords: правильные многоугольники; интерполяция функции; расчет площади